Production of bacteriocins by different enterococcal isolates - Lauková, A; Mareková, M (Folia microbiologica, 2001)
Bacteriocins produced by ruminal as well as environmental isolates were found to be heat-stable antimicrobial substances with a broad inhibitory spectrum (including Gram-negative species and sanitary-important species). The exponential phase of growth and pH 4-7 were optimal for their production. After purification, some of them were sequenced and specified.
Keywords: Microbial Sensitivity Tests; Feces; bachor; bakteriociny; mikrobiální testy citlivosti; Bacteria; Animals; feces; Listeria monocytogenes; Cattle; Humans; Rumen; lidé; zvířata; Bacteriocins; skot; Enterococcus